Pengembangan Model Permainan Tanpa Alat Untuk Mengembangkan Kemampuan Gerak Lokomotor dan Kerjasama Siswa Kelas III - Sari, Amara Nanda; Ansori, Isa (JURNAL PEDAGOGIK PENDIDIKAN DASAR, 2025)
This study aims to develop, validate, and test the effectiveness of a no-equipment game model to improve locomotor movement skills and collaboration among third-grade students at SD Negeri 2 Kebumen. The research employed a Research and Development (RD) method based on a simplified Borg Gall model. Data were collected through observation, interviews, questionnaires, tests, and documentation, and analyzed using descriptive and inferential statistical techniques. Expert validation results indicated that the no-equipment game model was highly feasible, with a feasibility score of 91.07%. Effectiveness testing revealed a significant improvement between pretest and posttest scores, with a significance value of 0.000 (0.05), and an N-Gain score of 0.599 categorized as moderate. Therefore, the no-equipment game model is considered effective and feasible for use in physical education classes to support the development of students’ basic motor skills and social collaboration abilities